THE SIGNIFICANCE OF INCREASING YOUTH SOCIAL ACTIVITY IN FORMING CIVIL SOCIETY - Yuldashov Ikromjon (Research Focus International Scientific Journal, 2022)
Nowadays, the democratic principles of the life of advanced countries are evaluated by the fact that they raise the human value to such a high level. At this point, the essence of fundamental changes and reforms taking place in our country comes from this principle. In the implementation of this principle, the formation of a new outlook and healthy thinking based on the harmony of national and universal values ​​is of great importance. It should be emphasized that the processes of democratic reforms implemented in the field of education in our society lead to the prioritization of universal values, despite the diversity of citizens' national-spiritual and educational potential and social activities. In this article, the importance of increasing the social activity of young people in the formation of civil society is scientifically researched.